The economics of ocean freight rates - Bennathan, Esra.; Walters, A. A. (New York : Praeger, 1969)
This book is based on a paper that the authors wrote in 1966 for an international seminar on shipping economics. Throughout this volume, the authors have tried to apply their understanding of the pricing behavior of the shipping industry to the problems of developing countries.
Includes bibliographical references: p. 131-135.
II 18/01/2019
Loans
Keywords: Shipping